2018
DOI: 10.30552/ejihpe.v8i1.225
|View full text |Cite
|
Sign up to set email alerts
|

Propiedades psicométricas del Centro de Estudios Epidemiológicos, Escala de depresión para adolescentes en Bulgaria

Abstract: En el presente estudio se evaluaron las propiedades psicométricas de la versión búlgara de la “Centre for Epidemiological Studies Depression Scale” (CES-DC), una escala auto-informada de 20 ítems diseñada para medir síntomas depresivos en niños y adolescentes. Un total de 700 adolescentes (323 niñas y 377 niños), de 13 a 17 años, participaron en el estudio. Además de la escala CES-DC, los adolescentes también contestaron el “Strength and Difficulties Questionnaire” (SDQ) y el “Spence Child Anxiety Scale” (SCAS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
1
2
0
Order By: Relevance
“…Contrary to existing studies [ 7 , 48 ] that reported higher depressive symptom scores in late adolescents, no age difference was observed in the general depression factor. This finding aligns with the results of Tsocheva et al‘s (2018) study [ 42 ]. Furthermore, in contrast to previous findings [ 18 ], late adolescents reported significantly lower levels of positive affect compared to early adolescents.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Contrary to existing studies [ 7 , 48 ] that reported higher depressive symptom scores in late adolescents, no age difference was observed in the general depression factor. This finding aligns with the results of Tsocheva et al‘s (2018) study [ 42 ]. Furthermore, in contrast to previous findings [ 18 ], late adolescents reported significantly lower levels of positive affect compared to early adolescents.…”
Section: Discussionsupporting
confidence: 93%
“…Concerning gender differences in depressive symptoms, a previous meta-analysis suggests that girls tend to report higher levels of depressive symptoms than boys [ 41 ]. In studies validating the CES-DC, girls generally report higher total scale scores and subscale scores for depressive affect and somatic symptoms compared to boys [ 18 , 20 , 42 ]. Yet, research on Chinese adolescents shows varied results; some studies find girls reporting more depressive symptoms [ 43 – 45 ], while a recent meta-analysis indicates no significant gender differences [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation